The ‘Postmodern Turn’ in the Social Sciences - Susen, Simon. author. aut Link
522 p.
Keywords: Simon Susen examines the impact of the 'postmodern turn' on the contemporary social sciences. On the basis of an innovative five-dimensional approach, this study provides a systematic, comprehensive, and critical account of the legacy of the 'postmodern turn', notably in terms of its continuing relevance in the twenty-first century. .